1988
DOI: 10.1007/bf00271588
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent potentiation of insulin release induced by alpha-ketoisocaproate and leucine in rats: possible involvement of phosphoinositide hydrolysis

Abstract: Summary. The ability of the amino acid leucine and its keto acid, alpha-ketoisocaproate, to induce insulin release, to initiate phosphoinositide hydrolysis, and to amplify the subsequent insulin secretory response to glucose was assessed. In islets whose inositol-containing lipids were prelabelled with myo [2-3H]inositol, the addition of either compound resulted in an increase in insulin output, an increase in 3H effiux, rapid and significant increases in labelled inositol phosphate accumulation and a sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…At least five experiments were conducted under each condition. activate one of the several isozymes of PLC identified in islets (13,15,19,38). Thus, MP shares this property with such diverse agonists as carbachol, acetylcholine, cholecystokinin, leucine, monomethylsuccinate, glucose, ␣-ketoisocaproate, and tolbutamide.…”
Section: Mp Induces Time-dependent Potentiation Of Insulinmentioning
confidence: 99%
See 2 more Smart Citations
“…At least five experiments were conducted under each condition. activate one of the several isozymes of PLC identified in islets (13,15,19,38). Thus, MP shares this property with such diverse agonists as carbachol, acetylcholine, cholecystokinin, leucine, monomethylsuccinate, glucose, ␣-ketoisocaproate, and tolbutamide.…”
Section: Mp Induces Time-dependent Potentiation Of Insulinmentioning
confidence: 99%
“…Because these latter stimulants for insulin secretion share in common many of the same stimulatory features of glucose on the beta cell, the concept that mitochondrial-derived signals mediate, at least in part, the stimulatory actions of the hexose has been proposed (11, 12). For example, both glucose and ␣-ketoisocaproate stimulate similar changes in insulin secretion and the calcium-dependent hydrolysis of islet phosphoinositide (PI) 1 pools and sensitize the beta cells to subsequent restimulation, a phenomenon also referred to as priming or time-dependent potentiation (TDP) (13)(14)(15).Standing at odds with this unifying concept, implicating the importance of mitochondrial signals in the regulation of secretion regardless of the nutrient molecule used, are studies with pyruvate. Although it seems to be well metabolized, pyruvate alone has no insulinotropic effect, although in combination with stimulatory glucose, a small stimulatory action has been described (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently proposed that the late response is the expression of the effect of a time-dependent regulatory loop on insulin release [2] and have demonstrated that this loop is functionally intact in islets from the spiny mouse [17], as it seems to be in glucose intolerant people [16]. The activation of protein kinase C by diacylglycerol has been proposed to be important for late phase insulin release and time-dependent potentiation [3,4,29]. In the case of Acomys islets, the previous activation of diacylglyceroldependent protein kinase C by glucose priming could, therefore, be the factor that improves the insulin response, bypassing the defective signal for first phase release.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of structurally distinct agonists, including glucose, -ketoisocaproate, monomethyl succinate and carbachol, activate phospholipase C (PLC) in islets (Axen et al 1983, Best & Malaisse 1983, Best 1986, Zawalich 1988b, MacDonald et al 1989, Zawalich et al 1989, Vadakekalam et al 1996. We next explored the potential influence of caloric restriction on PLC activation, monitored by IP accumulation in response to agonist addition.…”
Section: Ip Accumulation In Islets From Fed and Fasted Donorsmentioning
confidence: 99%